(untitled) (Conferencea, 2025)
We are witnessing a thrilling transformation in education, particularly in how we learn foreign languages. Artificial intelligence (AI) is no longer a futuristic concept but a concrete reality, altering traditional teaching methods and opening doors to incredibly personalized and captivating learning experiences. This article explores how AI is enhancing language acquisition, refining teaching techniques, and fostering a more dynamic and interactive learning environment. From AI-powered learning platforms to intelligent tutoring and automated assessment tools, we’ll explore how AI is transforming foreign language education, making it more effective and accessible than ever before.